PRAKTEK PEMBAYARAN HUTANG DENGAN BEKERJA PRESPEKTIF FIQH MUAMALAH (Studi Kasus di Jorong Malintang Nagari Lawang Mandahiling Kecamatan Salimpaung Kabupaten Tanah Datar) - Putri Handayani; Sulastri Caniago (Institut Agama Islam Negeri Batusangkar, 2021)
This study aims to explain the practice of paying debts by working in terms of fiqh muamalah in Jorong Malintang Nagari Lawang Mandahiling, Salimpaung District, Tanah Datar Regency. This research is a field research. The data sources consist of primary data sources, namely 7 people who owe, 7 people who give debts and 1 scholar, while secondary data sources are documentation and books and scientific works related to accounts payable. Data collection techniques that the author uses are interviews and documentation. The data analysis technique that the author uses is descriptive qualitative analysis. This study found that the implementation of debt payments by working carried out by the community in Jorong Malintang Nagari Lawang Mandahiling, Sallimpaung District, Tanah Datar Regency, namely debt and money receivables which was only done verbally without any written evidence. If it is due, but the borrower is unable to pay it and the payment is made by working in the person's field with his wages taken in exchange for the debt. The execution of debts paid by work is included in usury where the debtor takes the excess wages for working money when paying his debts.